Quinolone and Colistin Resistance Genes in Extended-Spectrum Beta-Lactamase (ESBL)-Producing Escherichia coli of Diverse Phylogenetic Groups Isolated from Seafood in Mumbai, India - Chandrashekar K. Dhanush; Manjusha Lekshmi; Shivani Kallappa Girisha; Binaya Bhusan Nayak; Sanath H. Kumar (Applied Microbiology)
Contamination of coastal-marine environment with multidrug-resistant Escherichia coli has resulted in such bacteria increasingly being detected in the seafood chain. This study aimed to determine the quinolone and colistin resistance genes in extended spectrum-β-lactamase (ESBL)-producing E. coli from seafood. ESBL-producing E. coli isolates (n = 269) were tested for quinolones and colistin resistance phenotypes by disk diffusion and broth microdilution methods, respectively. The isolates were further PCR screened for the plasmid-mediated quinolone resistance (PMQR) genes qnrA, qnrB, and qnrS, genomic mutations in gyrA and parC genes, and the colistin resistance genes mcr-1 and mcr-2. Phylogroup was determined by PCR using the Clermont E. coli phylotyping method. Of 269 isolates tested, 73.60% of E. coli isolates were resistant to moxifloxacin and 8.55% to ofloxacin, the least of all the quinolones tested. Further, 150 (55.76%) E. coli isolates carried at least one of the three PMQR genes tested, where qnrS was the most prevalent gene (53.90%). The colistin resistance gene (mcr-2) was detected in 38 (14.12%) isolates. Twenty-one of these isolates (55.26%) had a colistin minimum inhibitory concentration (MIC) of 16 µg/mL. Based on the Clermont E. coli phylotyping of the isolates harboring at least one of the qnr genes, 66 (44%) belonged to the phylogroup B1, followed by 23 (15.33%) to phylogroup A. Among 38 E. coli isolates carrying colistin resistance gene mcr-2, 27 (71.05%) isolates belonged to phylogroup B1, followed by 4 (10.52%) isolates to phylogroup A. The results suggest that E. coli phylogroups B1 and A harboring plasmid-mediated quinolone and colistin resistance genes are predominant in the seafood supply chain.